Optical Ultracompact Directional Antennas Based on a Dimer Nanorod Structure - Fangjia Zhu; María Sanz-Paz; Antonio I. Fernández-Domínguez; Mauricio Pilo-Pais; Guillermo P. Acuna (Nanomaterials, 2022)
Controlling directionality of optical emitters is of utmost importance for their application in communication and biosensing devices. Metallic nanoantennas have been proven to affect both excitation and emission properties of nearby emitters, including the directionality of their emission. In this regard, optical directional nanoantennas based on a Yagi–Uda design have been demonstrated in the visible range. Despite this impressive proof of concept, their overall size (~λ2/4) and considerable number of elements represent obstacles for the exploitation of these antennas in nanophotonic applications and for their incorporation onto photonic chips. In order to address these challenges, we investigate an alternative design. In particular, we numerically study the performance of a recently demonstrated “ultracompact” optical antenna based on two parallel gold nanorods arranged as a side-to-side dimer. Our results confirm that the excitation of the antiphase mode of the antenna by a nanoemitter placed in its near-field can lead to directional emission. Furthermore, in order to verify the feasibility of this design and maximize the functionality, we study the effect on the directionality of several parameters, such as the shape of the nanorods, possible defects in the dimer assembly, and different positions and orientations of the nanoemitter. We conclude that this design is robust to structural variations, making it suitable for experimental upscaling.